New arrangements for forest science to meet the needs of sustainable forest management - Byron, R.N.; Turnbull, J.W. (FORSPA, 1998)
This paper reviews the type of research which sustainable forest management (SFM) will need, and asks which institutions are best equipped and most likely to provide it, especially integrative policy, social and environmental research ?. There appears to be a contradiction: just when it is being recognised that there is an expanding need for more, better and better-integrated socio-economic and public policy research in support of SFM, many of the institutions which might have done that are being dismantled. We make a distinction between new SFM research and the "old style" production-oriented forestry research-output-enhancing or cost-reducing technological innovations which can (and perhaps should) be privatised and which has many attributes similar to long-term commercial consultancy. How many goverments or companies are willing to fund public policy research, environmental protection research; research which will challenge and question their economic, environmental and institutional policies?. How can a constituency for the type of "public interest' research inherent in SFM, be fostered?. How suitable is the process of tendering and competitive bids, for such kinds of public goods research ?